Estudo de diferentes métodos de extração de compostos bioativos e avaliação da atividade antioxidante da casca de café (Coffea arábica L.) - Silva, Mariana de Oliveira (2021)
Brazil is the world's largest coffee producer and exporter, with a strong impact on the country's economy. In view of this, the coffee culture gives rise to high volumes of waste, with emphasis on the husk. Coffee husks are characterized by exhibiting secondary metabolites, such as phenolic compounds, presenting themselves as raw material for obtaining bioactive compounds of interest in food. Therefore, the objective of the work was to evaluate different extraction methods (conventional solid-liquid with a temperature of 60 ºC in a water bath and unconventional assisted by ultrasound), ways of obtaining the raw material (in natura and dehydrated) and solutions extractors (100% water or 100% ethanol or a mixture of both 1: 1) of bioactive compounds from the coffee husk (Coffea arabica L.). The extracts were evaluated for their antioxidant potential using the 2,2-diphenyl-1- picrylhydrazil (DPPH •) scavenging activity assay, 2,2-azino-bis (3-ethylbezothiazoline) -6- acid scavenging activity sulfonic (ABTS ● +) and reduction to iron (FRAP) and later the quantification of total phenolic compounds, total flavonoids, condensed tannins and identification of major phenolic compounds by liquid chromatography was performed. It was found that the mixture of water and ethanol (1: 1) showed better extraction capacity of compounds with antioxidant activity and both methods, conventional and unconventional, showed satisfactory results. Added to this, it was also found that the best results were presented by the extracts that used the dehydrated raw material. The EBDM extract showed high antioxidant activity (84.95%, and 92.81%) for the DPPH and ABTS assays. Evaluating the content of total phenolic compounds (97.89 mg CAE / g) and condensed tannins (79.71 mg CE / g) in the extracts, corroborating with the results of antioxidant activities, in general, the best extraction solution was the mixture of water and ethanol (1: 1), using the dehydrated peel and conventional extraction as the best method, presenting higher levels of the bioactive compounds in question. For analysis of total flavonoids, in addition to the extract that used the solvent mixture, the extract obtained in water (15.69 mg CE / g) was highlighted in the extraction by the conventional method. However, from the analysis of the phenolic profile, the major compounds found in both extracts were gallic, caffeic and chlorogenic acid, the latter being the compound identified in the highest concentration (337.07 μg / g). Thus, the results obtained in this work demonstrate that the use of coffee husks proved to be efficient as a raw material for obtaining extracts rich in bioactive compounds with high antioxidant potential.